NICU Admissions for Meconium Aspiration Syndrome before and after a National Resuscitation Program Suctioning Guideline Change - Erika M. Edwards; Satyan Lakshminrusimha; Danielle E. Y. Ehret; Jeffrey D. Horbar (MDPI AG, 2019)
The Textbook of Neonatal Resuscitation, seventh edition, does not suggest routine endotracheal suctioning for non-vigorous infants born through meconium-stained amniotic fluid. We compared 301,150 infants at ≥35 weeks’ gestational age inborn at 311 Vermont Oxford Network member centers in the United States (U.S.) and admitted to neonatal intensive care units (NICU) who were born before (2013 to 2015) and after (2017) the guideline change. Logistic regression models adjusting for clustering of infants within centers were used to calculate risk ratios. NICU admissions for infants with a diagnosis of meconium aspiration syndrome (MAS) decreased from 1.8% to 1.5% (risk ratio: 0.82; 95% confidence interval: 0.68, 0.97) and delivery room endotracheal suctioning in this group decreased from 57.0% to 28.9% (0.51; 0.41, 0.62). Treatment with conventional or high frequency ventilation, inhaled nitric oxide, or extracorporeal membrane oxygenation remained unchanged 42.3% vs. 40.3% (0.95; 0.80, 1.13) among infants with MAS and 9.1% vs. 8.2% (0.91; 0.87, 0.95) among infants without MAS. The use of surfactant among infants with MAS increased from 24.6% to 30% (1.22; 1.02, 1.48). Mortality (2.6 to 2.9%, 1.12; 0.74, 1.69) and moderate/severe hypoxic-ischemic encephalopathy (5.4 to 6.8%, 1.24; 0.91, 1.69) increased slightly in 2017. Subgroup analyses of infants with 1 min Apgar scores of ≤3 found similar results. While NICU admissions for MAS and tracheal suctioning decreased after the introduction of the new guideline with no subsequent increase in severe respiratory distress among infants with and without a MAS diagnosis, limitations in our study preclude inferring that the new guideline is safe or effective.